Упростить дроби: 4y-5/10 - 6y+3/10= -4a+3/20 - a-7/20= b+3a/a^2 - b-2a/a^2= 2+x/2x-14 - x-2/2x-14= y+2/6-y + y+2/y-6= y^2-z/y-z - z^2-z/y-z= (/-знак дроби;^-знак степени(y^2-y в квадрате))

Упростить дроби: 4y-5/10 - 6y+3/10= -4a+3/20 - a-7/20= b+3a/a^2 - b-2a/a^2= 2+x/2x-14 - x-2/2x-14= y+2/6-y + y+2/y-6= y^2-z/y-z - z^2-z/y-z= (/-знак дроби;^-знак степени(y^2-y в квадрате))
Гость
Ответ(ы) на вопрос:
Гость
4у-5/10 -6у+3/10= =(4у-5-6у-3)/10=(-2у-8)/10= =2(-у-4)/10=(-у-4)/5 -4а+3/20 -а-7/20= =(-4а+3-а+7)/20=(10-5а)/20= =5(2-а)/20=(2-а)/4 б+3а/а^2 -б-2а/а^2= =(б+3а-б+2а)/а^2=5а/а^2=5/а 2+х/2х-14 -х-2/2х-14= =(2+х-х+2)/2(х-7)=4/2(х-7)= =2/(х-7) у+2/6-у +у+2/у-6= =(у+2-у-2)/(6-у)=0 у^2-з/у-з -з^2-з/у-з= =(у^2-з-з^2+з)/у-з= (у^2-з^2)/(у-з)= =(у-з)(у+з)/(у-з)=у+з
Не нашли ответ?
Ответить на вопрос
Похожие вопросы